Using of Visual Application in Arabic Language Learning Class X MAN 1 Kuantan Singingi - Amrina Amrina; Ihwatu Akhiri; Chuen Lee; Jansee Jansee (Yayasan Adra Karima Hubbi, 2022)
This article is a utilization research that really needs literacy and reading materials in describing a discussion, which is through knowledge of the background of an incident, and relies on research methods. This article is about using the Canva application as a medium for learning Arabic, which was conducted at MAN 1 Kuantan Singingi. Learning media is something that is very much needed by educators in supporting education, the media offers many conveniences for its users, both educators and students. Plus during this pandemic, educators are required to be able or master about media in education. Especially in this sophisticated era, not only educators, even everyone is required to understand and be able to use technology appropriately and correctly, this Canva application is no exception. Canva is an application that can be accessed via mobile phones, with various and interesting features, with the Canva application both educators and students can use the Canva application and develop their own creativity.